2013
DOI: 10.1016/s0924-9338(13)75791-2
|View full text |Cite
|
Sign up to set email alerts
|

465 – Effect of transactional analysis education to nurses on patients’ satisfaction

Abstract: Introduction:Patient satisfaction is an important indicator of quality of care and health facilities. It is a predictor of patient willingness to follow treatment regimen.Objectives:Patient perception of nurse caring has been associated with positive patient outcomes, better postoperative functional status and less symptom distressAims:To determine efficacy of transactional analysis training on inpatient‘s satisfaction of nurses.Methods:This study was performed as a double blind, experimental design with parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Nurses who are more caring employ more patient-centered caring skills in clinical practice, and patients feel more cared for and satisfied with the nursing care [18]. Educational programs enhance nurses' caring knowledge and practical competence to ensure that patients are willing to receive treatment, thereby enhancing patient satisfaction [16] [19]. The results of this study revealed that the scores of nurse caring and patient satisfaction significantly increased between the pretest and the posttest.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nurses who are more caring employ more patient-centered caring skills in clinical practice, and patients feel more cared for and satisfied with the nursing care [18]. Educational programs enhance nurses' caring knowledge and practical competence to ensure that patients are willing to receive treatment, thereby enhancing patient satisfaction [16] [19]. The results of this study revealed that the scores of nurse caring and patient satisfaction significantly increased between the pretest and the posttest.…”
Section: Discussionmentioning
confidence: 78%
“…In an experimental study, Yeakel and colleagues (2003) [15] examined the impact of patient satisfaction after nurses participated in a multifaceted staff intervention; the results showed that the patients admitted after the intervention judged nurses as more caring and reported greater satisfaction than did patients admitted before the intervention. Sheikhmooesi et al (2013) [16] investigated the efficacy of a caring education program for nurses on inpatient satisfaction and found that the intervention program significantly improved inpatient satisfaction (p < 0.05).…”
Section: Introductionmentioning
confidence: 99%